ELECTRONS IN FELDSPAR I: ON THE WAVEFUNCTION OF ELECTRONS TRAPPED AT SIMPLE LATTICE DEFECTS - Poolton N.R.J.; Wallinga J.; Murray A.S.; Bulur E.; Bøtter-Jensen L. (My University, 2002)
The purpose of this article is to make an initial consideration of the physical properties of electrons trapped at classic hydrogenic lattice defects in feldspar. We are particularly interested to determine the radial extent of the electron wavefunctions in the ground and excited states. It is shown that for NaAlSi3O8, the ground-state wavefunction is expected to be confined well within a single lattice unit cell, but the first excited state is far more extensive, being spread over several unit cells. This aspect is of direct relevance to understanding the nature of various luminescence processes in the materials. Under low-energy optical stimulation (hν∼ 1.4 eV), luminescence can be a competitive process between direct electron-hole tunnelling recombination (with the charge still trapped at the defect sites), and free-to-bound recombination (after the excited state electron accesses the conduction band). We show that analysis of the thermal behaviour of the luminescence can be used to separate the two processes.